Comparison of the Expansion and End of The World in The Qur’an and New Science - Ashna, Asadullah (Integrated Journal for Research in Arts and Humanities, 2024)
Comparison of the expansion and end of the world in the Qur’an and new science is one of the important issue and this comparison is quite vital to be considered. In this article, according to the scientific information of the Quran, which corresponds to the findings of contemporary scientists, we have investigated black holes. Black holes form when a star uses up all its fuel. A black hole is a point of space with so much gravity and density that even light cannot escape. This attraction is so strong that it compresses all matter into a small space. According to the theory of general relativity, matter that is compressed enough can bend space-time and form a black hole. The black hole's point of no return is called the event horizon. Black holes do not reflect any light. But they can be identified based on the effects they have on the materials and objects around them. Fourteen centuries ago, when science and astronomy were still very primitive, the fact that the sun and the stars will one day lose their light has been stated in numerous Quranic verses.